Quick Chain Rule Question

I have a homework problem similar to this, but I was unsure about the example in the book:

Find $\displaystyle F'(z)$ if $\displaystyle F(z) = (2z + 5)^3(3z - 1)^4$

The solution steps are as follows:

$\displaystyle F'(z) = (2z + 5)^3 \times 4(3z - 1)^3(3) + (3z - 1)^4 \times 3(2z + 5)^2(2)$

$\displaystyle = 6(2z + 5)^2(3z - 1)^3[2(2z + 5) + (3z - 1)]$

$\displaystyle = 6(2z + 5)^2(3z - 1)^3(7z + 9)$

I get a little lost during the second step, and where did that 6 come from?